2011
DOI: 10.1167/iovs.11-7818
|View full text |Cite
|
Sign up to set email alerts
|

Equivalence of Biomechanical Changes Induced by Rapid and Standard Corneal Cross-linking, Using Riboflavin and Ultraviolet Radiation

Abstract: Rapid UV cross-linking treatment can be regarded as equivalent to the standard procedure in terms of increase in corneal stiffness. The new rapid protocol shortens the treatment duration by more than two thirds, from 30 to 9 minutes. The safety of the higher intensities must be addressed in further clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
109
1
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(122 citation statements)
references
References 17 publications
4
109
1
4
Order By: Relevance
“…Stress-strain measurements on porcine corneal strips treated using a rapid protocol (9 min at 10 mW/cm 2 ) demonstrated equivalent increases in corneal stiffness in comparison with the standard protocol. 30 In a recent prospective randomised trial, 31 contralateral eyes of 21 patients with progressive keratoconus were randomised to either conventional or rapid CXL (7 mW/cm 2 for 15 min). A halt in ectasia progression was seen in all cases at a mean follow-up of 46 months.…”
Section: Rapid Crosslinkingmentioning
confidence: 99%
“…Stress-strain measurements on porcine corneal strips treated using a rapid protocol (9 min at 10 mW/cm 2 ) demonstrated equivalent increases in corneal stiffness in comparison with the standard protocol. 30 In a recent prospective randomised trial, 31 contralateral eyes of 21 patients with progressive keratoconus were randomised to either conventional or rapid CXL (7 mW/cm 2 for 15 min). A halt in ectasia progression was seen in all cases at a mean follow-up of 46 months.…”
Section: Rapid Crosslinkingmentioning
confidence: 99%
“…8,9 Conventional epithelium-off crosslinking (CXL) demonstrated its safety and long-term efficacy in stabilizing progressive keratoconus and secondary ectasias in different clinical trials. [10][11][12][13][14] On the other hand, the procedure is time consuming, lasting from 40 min to 1 h. 15 The Bunsen-Roscoe's law of reciprocity [16][17][18] theoretically demonstrated that the photochemical process behind crosslinking depends on the absorbed UV-A energy and its biological effect is proportional to the total energy dose delivered in the tissue. [16][17][18] According to this concept, it is theoretically possible to deliver the same energy dose ensuring a proportional biological effect by setting different UV-A powers and exposure times in order to accelerate and shorten the crosslinking procedure in accelerated crosslinking (ACXL) modality.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] On the other hand, the procedure is time consuming, lasting from 40 min to 1 h. 15 The Bunsen-Roscoe's law of reciprocity [16][17][18] theoretically demonstrated that the photochemical process behind crosslinking depends on the absorbed UV-A energy and its biological effect is proportional to the total energy dose delivered in the tissue. [16][17][18] According to this concept, it is theoretically possible to deliver the same energy dose ensuring a proportional biological effect by setting different UV-A powers and exposure times in order to accelerate and shorten the crosslinking procedure in accelerated crosslinking (ACXL) modality. [17][18][19] According to photochemical crosslinking studies based on kinetics model 7 the UV-A illumination caused a rapid depletion of oxygen in a riboflavin-soaked cornea and turning the UV light off led to replenishment of the oxygen to its original level within 3 to 4 min.…”
Section: Introductionmentioning
confidence: 99%
“…5 Although the Bunden-Roscoe reciprocity law may be valid for a certain dose range and therefore a true linear relationship between dose and time is unlikely to exist, the radicals that generate the cross-links are formed in a shorter period of time when the radiation intensity is increased from 3 to 10 mW/cm 2 . 6 Initial studies, performed on porcine eyes, showed that accelerated CXL performed at 10 mW/cm 2 for 9 min was equivalent to conventional CXL in biomechanical stiffness. 6,7 When the cornea is treated with conventional CXL a demarcation line is seen at B300 mm.…”
mentioning
confidence: 99%
“…6 Initial studies, performed on porcine eyes, showed that accelerated CXL performed at 10 mW/cm 2 for 9 min was equivalent to conventional CXL in biomechanical stiffness. 6,7 When the cornea is treated with conventional CXL a demarcation line is seen at B300 mm. 8,9 This demarcation line, seen in anterior segment optical coherence tomography (AS-OCT), demonstrates the depth of treatment with the corneal stroma lying anterior to this demarcation line that has been cross-linked and hence strengthened.…”
mentioning
confidence: 99%